Food Grains Enquiry, Government of India - Planning Commission (Planning Commission, 1957)
The market level questionnaire should be canvassed in the market which is the most important for disposal of the food-grains of the block. This market may be outside the boundaries of the block. If there is no permanent market in or near the block, the Questionnaire may be canvassed at the weekly market or at a place having the most important concentration of grain merchants.
Government of India